European Society of Organ Transplantation (ESOT) Consensus Statement on Machine Perfusion in Cardiothoracic Transplant - Cristiano Amarelli; Irene Bello; Clemens Aigner; Marius Berman; Massimo Boffini; Stephen Clark; Marita Dalvindt; Julien de Wolf; Stephan Ensminger; David Gomez de Antonio; Lucas Hoyos; Lucrezia Palmieri; et al. (Transplant International)
The machine perfusion (MP) of transplantable grafts has emerged as an upcoming field in Cardiothoracic (CT) transplantation during the last decade. This technology carries the potential to assess, preserve, and even recondition thoracic grafts before transplantation, so it is a possible game-changer in the field. This technology field has reached a critical turning point, with a growing number of publications coming predominantly from a few leading institutions, but still need solid scientific evidence. Due to the increasing need to expand the donor pool, especially in Europe, where the donor age is steeply increased, a consensus has been established to address the growing need and knowledge of machine perfusion in cardiothoracic transplantation, targeting the unmet scientific need in this growing field but also, priorities for development, and regional differences in utilization rates and organizational issues. To address MP in CT, the European Society of Organ Transplantation (ESOT) convened a dedicated Working group comprised of experts in CT to review literature about MP to develop guidelines that were subsequently discussed and voted on during the Consensus Conference that took place in person in Prague during the TLJ 3.0 in November 2022. The findings and recommendations of the Cardiothoracic Working Group on MP are presented in this article.